Annual variations of abundance, egg production rate, and community structure of Oithona similis in Jiaozhou Bay, the Yellow Sea. - Yin, J.H., C.C. Wu, P.P. Shen, A.Y. Wan, Z.C. Tao & Y.T. Wang (Frontiers In Marine Science, 2023)
In marine ecosystems, copepods (<2 mm) play an important role in the transfer of carbon and energy to higher tropic levels. Investigations in Jiaozhou Bay were carried out throughout 2017-2018, combined with laboratory experiments. The annual abundance, egg production, female prosome length, female carbon mass, clutch size, population composition, and development time of Oithona similis at different temperatures were analyzed to assess the life strategies and estimate generation cycles of O.similis in typical temperate regions at mid-latitude, represented by Jiaozhou Bay. The results include: 1) O.similis abundance was characterized by bimodal cycles, with the major peak in winter (1471 +/- 206 ind/m(3)) and the minor peak in spring (740 +/- 320 ind/m(3)). O. similis abundance was not subject to food limitations except in January. The lower abundance was mainly affected by temperature (>20 degrees C) and low salinity in August. Predation from large size zooplankton was one of the factors in regulating O. similis abuncance in Jiaozhou Bay. 2) Over the year, the egg production rate, female prosome length, and female carbon mass of O.similis ranged from 0.03 +/- 0.02 to 1.21 +/- 0.25 eggs female(-1)d(-1), 410 +/- 6 to 472 +/- 4 mu m, and 0.35 +/- 0.05 to 0.43 +/- 0.03 mu g c female(-1) respectively. Female prosome length, and female carbon were both significantly negative correlated with temperature(P<0.01). The clutch size of O.similis varied between 4 and 21 and we did't find it was related with other factors. 3) O. similis appeared at almost all stages, and reproduced continuously throughout the year. According to the sex ratio of O.similis and other factors, we inferred that O. similis produced four generations per year in Jiaozhou Bay.